2019
DOI: 10.11606/issn.1679-9836.v98i4p241-253
|View full text |Cite
|
Sign up to set email alerts
|

What does immunology have to do with brain development and neuropsychiatric disorders?

Abstract: Introduction: Neural development is an enormously complex and dynamic process. From very early in brain development ‘immune cells’ play a key role in a number of processes including the formation and refinement of neural circuits, as well as sexual differentiation. There is a growing body of evidence that the immune system also plays an important role in the pathobiology of several neurodevelopmental and neuropsychiatric disorders. Objective: The goal of this article is to review the currently available data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 182 publications
0
1
0
Order By: Relevance
“…3 Although the pathophysiology behind is unclear there is some evidence indicating that the immune system plays a key role in the development of several neuropsychiatric disorders. 4 O'Connor et al reported that psychological factors such as depressive and anxiety symptoms predict the immune response to the meningococcal vaccine. 5 Guloksuz et al in their pilot case-control study showed a temporal relationship between the new onset of neuropsychiatric disorders and the time of vaccination.…”
mentioning
confidence: 99%
“…3 Although the pathophysiology behind is unclear there is some evidence indicating that the immune system plays a key role in the development of several neuropsychiatric disorders. 4 O'Connor et al reported that psychological factors such as depressive and anxiety symptoms predict the immune response to the meningococcal vaccine. 5 Guloksuz et al in their pilot case-control study showed a temporal relationship between the new onset of neuropsychiatric disorders and the time of vaccination.…”
mentioning
confidence: 99%